Belt and Road Construction’s Achievement of the Past Decade and Development Prospect - Liyong , Wang; Yongliang, Lin (Napredak, 2024)
Ten years ago, with deep insight into global development trends and to promote common development and human progress, General Secretary Xi Jinping put forward the grand Belt and Road Initiative. Now it can be concluded that it is a successful and globally important project which has advanced world economy, but also created a brand-new model of international cooperative development. This text offers a series of concrete data: for example, China has signed MoUs for the Digital Silk Road with 17 countries, established bilateral cooperation mechanisms for “Silk Road” e-commerce with 23 countries and built 34 cross-border terrestrial cable systems and several international submarine cables. More importantly, numerous forms of integration have been realized between those countries, from cooperation in culture, education, tourism, science and technology to the construction and expansion of transport infrastructure. Thanks to the open and partnering relationship, the paradigm of international cooperation development has been changed, which announces a prospect of expanding the cooperation domain with new projects such as the “Green Silk Road”, the “Digital Silk Road” and the “Health Silk Road”. It implies a new way of thinking and approach to the values, rules and standards, and the promotion of new technologies such as artificial intelligence, big data, cloud computing, and Internet of Things.